2008
DOI: 10.1007/s11481-008-9138-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Impairs Blood–Brain Barrier P-glycoprotein Function in Mice Through Prostaglandin- and Nitric Oxide-Independent Pathways

Abstract: P-glycoprotein (P-gp) is a brain-to-blood efflux system that controls the ability of many drugs and endogenous substances to access the brain. In vitro work has shown that inflammatory states mediated through lipopolysaccharide (LPS) and tumor necrosis factor-alpha first impair and then stimulate P-gp activity. Here, we determined whether LPS can affect P-gp function in vivo. Mice treated with a single intraperitoneal injection of LPS (3 mg/kg) showed an inhibition of P-gp function. As assessed by brain perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 21 publications
4
59
1
Order By: Relevance
“…We did not reassess the effects of S. enterica LPS on the brain uptake of [ 14 C]sucrose or colistin in the current study, as previous results in our laboratory have demonstrated the effects of S. enterica LPS to be quite reproducible (with a coefficient of variation of 12.2% over 24 replicates) and consistent with reports from other laboratories (28,29). The lack of effect of P. aeruginosa LPS is consistent with our previous observations demonstrating that inoculation of P. aeruginosa did not affect the paracellular integrity of the BBB (15), despite the plasma concentrations of IL-6 and TNF-␣ being substantially increased with both P. aeruginosa inoculation and P. aeruginosa LPS administration.…”
Section: Discussionsupporting
confidence: 84%
“…We did not reassess the effects of S. enterica LPS on the brain uptake of [ 14 C]sucrose or colistin in the current study, as previous results in our laboratory have demonstrated the effects of S. enterica LPS to be quite reproducible (with a coefficient of variation of 12.2% over 24 replicates) and consistent with reports from other laboratories (28,29). The lack of effect of P. aeruginosa LPS is consistent with our previous observations demonstrating that inoculation of P. aeruginosa did not affect the paracellular integrity of the BBB (15), despite the plasma concentrations of IL-6 and TNF-␣ being substantially increased with both P. aeruginosa inoculation and P. aeruginosa LPS administration.…”
Section: Discussionsupporting
confidence: 84%
“…This is in contrast to findings in astrocyte-enriched cultures with no cocultivation, where TLR4 is expressed rather sparsely and is more difficult to induce. Although LPS normally does not readily pass the intact BBB, LPS itself can impair the integrity of the BBB and thereby affect the flux system between blood and brain (44). Therefore, although our findings in the present study must primarily be conceived as purely in vitro model data, they may have some bearing also for the understanding of in vivo systemic actions following the release of LPS (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have reported that Abcb1 gene expression can be regulated by various factors such as steroid hormones (Nuessler et al 1997, Nakayama et al 1999, cellular membrane stretch (Sardini et al 1994, Wang et al 2013, and inflammation (Salkeni et al 2009, Poller et al 2010, Gibson et al 2012. P4 is the major regulatory hormone of pregnancy, essential for the maintenance of pregnancy and uterine growth (Thijssen 2005).…”
Section: Discussionmentioning
confidence: 99%